Athletes and parents coping with deselection in competitive youth sport: A communal coping perspective. (May 2017) - Neely, Kacey C.; McHugh, Tara-Leigh F.; Dunn, John G.H.; Holt, Nicholas L.
Abstract: Objective: The purpose of this study was to examine how female adolescent athletes and their parents cope with deselection from provincial sport teams using a communal coping perspective. Method: Individual semi-structured interviews were conducted with 14 female adolescent athletes ( M age = 15.0 years; SD  = 1.4) and 14 of their parents (5 fathers, 9 mothers; M age = 45.2 years; SD  = 5.4). Participants were deselected from provincial soccer ( n  = 4), basketball ( n  = 5), volleyball ( n  = 2), and ice hockey ( n  = 3) teams. Data were analyzed using a descriptive phenomenological approach (Giorgi, 2009) guided by a framework of communal coping (Lyons, Mickelson, Sullivan, & Coyne, 1998). Results: Participants appraised deselection from a shared perspective (i.e., athletes and parents viewed deselection as 'our problem') and the responsibility for coping with deselection changed as time progressed. Initially, parents protected their daughters from the negative emotions arising from deselection (an 'our problem, my responsibility' orientation). Athletes and parents then engaged in cooperative actions to manage their reactions to the stressor (an 'our problem, our responsibility' orientation). Finally, athletes and parents engaged in individual coping strategies, again reflecting an 'our problem, my responsibility' orientation but with athletes taking more responsibility for coping. Conclusion: This study demonstrated the value of using a communal coping perspective to understand interpersonal dimensions of coping in sport, and revealed forms and processes of communal coping used by athletes and their parents. Highlights: Athletes and parents perceived deselection as a shared stressor. The responsibility for coping with deselection and its consequences changed as time progressed. Initially, parents tried to protect their daughters from negative emotions. Athletes and parents then engaged in cooperative coping actions. Finally, athletes focused on their club team and increased their training efforts.